ANALYSIS OF SLANG IN THE NOVEL MARMUT MERAH JAMBU BY RADITYA DIKA AS INDONESIAN LANGUAGE TEACHING MATERIALS IN SENIOR HIGH SCHOOL - Sobri; Safi'i, Imam; Dwi Astuti, Maulia (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2024)
This research aims to describe the formation Slang vocabulary in the novel Marmut Merah Jambu. The method used in this research is descriptive qualitative. The data collection technique used is the observation technique, technique notes, and library techniques. The data source in the research is the vocabulary in the novel Marmut Merah Jambu by Raditya Dika which is in the form of Slang. Data analysis uses content analysis techniques (content study). Based on the results of the data analysis that has been carried out, this research produced 46 findings data. The research data on the formation of Slang vocabulary can be detailed as follows: (1) insertion of -ok- in 2 data; (2) uptake of the Jakarta (Betawi) dialect with 9 data; (3) acronyms with 12 data; (4) 3 data abbreviations; and (5) use of other terms totaling 20 data.